2019
DOI: 10.1177/2040620719844697
|View full text |Cite
|
Sign up to set email alerts
|

Update on the role of venetoclax and rituximab in the treatment of relapsed or refractory CLL

Abstract: For the treatment of mature B cell malignancies including chronic lymphocytic leukemia (CLL), the last 5 years has brought major advances in the application of targeted therapies. Whilst monoclonal anti-CD20 agents such as rituximab have a central role in combination with traditional cytotoxic therapy, their combination with novel agents that target the B cell receptor signaling pathway and other intracellular mechanisms of B cell proliferation is a new approach to treatment. Venetoclax is a highly specific no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 45 publications
(66 reference statements)
0
2
0
Order By: Relevance
“…Synergistic drug combinations can be rationalized using knowledge of single-drug action mechanisms. Venetoclax (ABT-199) is an FDA-approved selective Bcl-2 inhibitor for the treatment of CLL and AML 11 , 12 , 63 , 64 . However, venetoclax has limited potency in the treatment of lung cancer.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Synergistic drug combinations can be rationalized using knowledge of single-drug action mechanisms. Venetoclax (ABT-199) is an FDA-approved selective Bcl-2 inhibitor for the treatment of CLL and AML 11 , 12 , 63 , 64 . However, venetoclax has limited potency in the treatment of lung cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, the BH3-mimetic specific Bcl2 inhibitor venetoclax (ABT-199), designed to selectively bind and inhibit Bcl-2 protein, has been approved by the FDA for the treatment of patients who have relapsed or refractory chronic lymphocytic leukemia (CLL) with a genetic abnormality known as 17p deletion. However, there remains a small proportion of patients, in the range of 15-25%, who develop venetoclax failure with either venetoclax monotherapy or the venetoclax/rituximab combination 11 , 12 . In addition to CLL, clinical trials have demonstrated the clinical benefit of venetoclax-based therapies in newly diagnosed acute myeloid leukemia (AML), leading to the recent FDA approval of venetoclax in combination with hypomethylating agents or low-dose cytarabine for older adults with newly diagnosed AML 13 .…”
Section: Introductionmentioning
confidence: 99%